Deconstructing Feminist Positions in Unigwe’s “Possessing The Secret Of Joy” and Aidoo’s “The Girl Who Can” - Confidence Gbolo Sanka; Peter Arthur; Samuelis Gracious Abla (Journal of Language and Literature, 2021)
For many years, African women have been blaming men for the inferior position of the female gender in African societies. In this blame game, the patriarchal and cultural stipulations of societies are not left out since they present the male gender as superior. This observation is emphasised by the myriads of texts on feminism which largely present discourses that highlight the roles of the male gender and patriarchy in perpetuating female otherness. In doing so, the females are portrayed as mere victims who do not play any active roles in this ordeal and are therefore exonerated from blame. This notwithstanding, a close study of events in patriarchal societies and the evolving contemporary current of thought in feminist domains questions the portrayal of women as helpless victims of patriarchy. By using the theories of feminism and deconstruction and by focusing on the themes and language of the stories, this paper seeks to unearth some patterns in Unigwe’s “Possessing the Secret of Joy” and Aidoo’s “The Girl Who Can” which speak to the involvement of women as agents of patriarchy. It also argues that some of the time too, men can be victims or subjugates of patriarchy in the African context. The paper concludes that the fight against patriarchy remains the lot of both genders and not in the blame game.